DIVERSITY OF WILD PALMS (ARECACEAE) IN THE REPUBLIC OF BENIN: FINDING THE GAPS IN THE NATIONAL INVENTORY COMBINING FIELD AND DIGITAL ACCESSIBLE KNOWLEDGE - Idohou, Rodrigue; Arino, Arturo; Assogbadjo, Achille; Glele Kakai, Romain; Sinsin, Brice (Biodiversity Informatics, 2015)
Despite many efforts by researchers worldwide to assess the biodiversity of plant groups, many locations on Earth remain not well surveyed and data-deprivation biases often occur. Robust estimates of inventory completeness could help alleviate the problem. This study aimed at identifying areas representing gaps in current knowledge of African palms, with a focus on Benin (West Africa). We assessed the completeness of knowledge of African palms targeting geographical distance and climatic difference from well-known sites. Data derived from intensive fieldwork were combined with independent data available online. Completeness inventory indices were calculated and coupled with other criteria to decide on the extent of knowledge. Results showed a high overall value for inventory completeness, as well as an even distribution of well-known areas across the country. However, poorly-known areas were distinctly identified and correlated to remote locations with low accessibility. This study illustrates how biodiversity survey and inventory efforts can be guided by existing knowledge. We strongly recommend the combination of digital accessible knowledge and fieldwork, coupled with expert knowledge, to obtain a better picture of the completeness of the inventory in tropical ecosystems.